2016
DOI: 10.1016/j.jpowsour.2015.10.047
|View full text |Cite
|
Sign up to set email alerts
|

Electro-thermal impedance spectroscopy applied to an open-cathode polymer electrolyte fuel cell

Abstract: The development of in-situ diagnostic techniques is critical to ensure safe and effective operation of polymer electrolyte fuel cell systems. Infrared thermal imaging is an established technique which has been extensively applied to fuel cells; however, the technique is limited to measuring surface temperatures and is prone to errors arising from emissivity variations and reflections. Here we demonstrate that electro-thermal impedance spectroscopy can be applied to enhance infrared thermal imaging and mitigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 17 publications
0
23
0
Order By: Relevance
“…Thermocouples can provide a crude measure of temperature inside fuel cells [15][16][17][18], but cannot provide high spatial resolution, and as they need to be inserted inside the fuel cell, this often requires design modifications which may affect reactant flow and fuel cell performance. Infrared thermal imaging can provide very high spatial and temperature resolution [19][20][21][22][23][24], but requires use of modified fuel cells with an infrared transparent window, and/or cells with open channels (such as open-cathode fuel cells [25][26][27][28]) or can only image the outer surface of a cell or stack [29,30]. Combined temperature and current mapping studies allow the impact and interactions of these two parameters on the overall performance to be assessed [17,20,[31][32][33].…”
Section: Current and Temperature Mapping In Fuel Cellsmentioning
confidence: 99%
“…Thermocouples can provide a crude measure of temperature inside fuel cells [15][16][17][18], but cannot provide high spatial resolution, and as they need to be inserted inside the fuel cell, this often requires design modifications which may affect reactant flow and fuel cell performance. Infrared thermal imaging can provide very high spatial and temperature resolution [19][20][21][22][23][24], but requires use of modified fuel cells with an infrared transparent window, and/or cells with open channels (such as open-cathode fuel cells [25][26][27][28]) or can only image the outer surface of a cell or stack [29,30]. Combined temperature and current mapping studies allow the impact and interactions of these two parameters on the overall performance to be assessed [17,20,[31][32][33].…”
Section: Current and Temperature Mapping In Fuel Cellsmentioning
confidence: 99%
“…For example, the relationship between electrochemical performance and heat generation, using so-called electro-thermal impedance spectroscopy, has been reported [6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported the efficiency of these polymeric electrolytes based on thermoplastic polymers and ILs for use in electrochemical devices . Peng et al .…”
Section: Introductionmentioning
confidence: 99%
“…used thermoplastic polyurethane and poly(vinylidene‐ co ‐hexafluoropropylene) with a lithium salt for construction of an electrolyte for batteries, obtaining an electrolyte with high conductivity, 6.62 × 10 −3 S cm −1 , and good mechanical stability at room temperature. Thermoplastic polyurethanes were also used to produce supercapacitors with high capacitance and high potential windows . A great drawback of using thermoplastic as polymer electrolytes is their working temperature range, which is limited to the melting point of the polymeric matrix.…”
Section: Introductionmentioning
confidence: 99%